2016
DOI: 10.1186/s12929-016-0225-8
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol induces cytostasis of cortical basal progenitors

Abstract: BackgroundDeveloping brain is a major target for alcohol’s actions and neurological/functional abnormalities include microencephaly, reduced frontal cortex, mental retardation and attention-deficits. Previous studies have shown that ethanol altered the lateral ventricular neuroepithelial cell proliferation. However, the effect of ethanol on subventricular basal progenitors which generate majority of the cortical layers is not known.MethodsWe utilized spontaneously immortalized rat brain neuroblasts obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 62 publications
1
21
1
Order By: Relevance
“…Thus, ethanol exposure in vivo may target cells in the phases of the cell cycle other than the S phase. This is consistent with the efects of prenatal exposure to ethanol on cortical proliferative zones in vivo (Miller and Nowakowski, 1991;Miller and Kuhn, 1995) and neural stem cells in vitro (Higgins and Borenfreund, 1986;Santillano et al, 2005;Hicks et al, 2010;Riar et al, 2016) in which ethanol principally afects cells passing through the G1 phase. Note, however, that a recent analysis does show that the S phase of proliferating hippocampal cells of adult rats is more than halved following exposure to ethanol (McClain et al, 2011).…”
Section: Figuresupporting
confidence: 79%
“…Thus, ethanol exposure in vivo may target cells in the phases of the cell cycle other than the S phase. This is consistent with the efects of prenatal exposure to ethanol on cortical proliferative zones in vivo (Miller and Nowakowski, 1991;Miller and Kuhn, 1995) and neural stem cells in vitro (Higgins and Borenfreund, 1986;Santillano et al, 2005;Hicks et al, 2010;Riar et al, 2016) in which ethanol principally afects cells passing through the G1 phase. Note, however, that a recent analysis does show that the S phase of proliferating hippocampal cells of adult rats is more than halved following exposure to ethanol (McClain et al, 2011).…”
Section: Figuresupporting
confidence: 79%
“…Second, the cortex-wide reduction of DNA methylation may be biased toward the lower cortical layers due to inherent cell number. Third, in light of several reports (Prock & Miranda, 2007; Riar et al, 2016) demonstrating a developmental delay of cortical progenitors devoid of apoptosis, it can be presumed that cellular density in the CP may be more compacted than in untreated CPs (see Fig. 6), thereby skewing the immunohisto-chemical abundance of DNA methylation markers.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, one group has reported that alcohol-induced depletion of neural stem cells (and by default, their proliferation) is not due to neuroepithelial cell apoptosis, but rather is due to a premature transformation of the NEs into radial glial-like cells (Camarillo & Miranda, 2008). Another group has proposed that reduced progenitor proliferation may be the result of cytostasis, or cell cycle arrest in the absence of apoptosis (Riar et al, 2016). Whichever the case, the apparent result would denote a higher number of cells remaining in the VZ/SVZ, meaning that these cells do not survive past differentiation or represent a delay in development, given the similarities between the E17 alcohol-exposed cortex and E16 controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the E concentration used herein approximated those that were widely used to elicit a range of neurotoxic responses in various mouse and rat models [ 7 , 66 , 72 ]. E-treated plates were incubated for 24 h in an alcohol-pre-saturated incubator by placing a beaker filled with E for 24 h to prevent evaporation and maintain E concentrations in the culture media [ 69 , 73 ], while the control cells were maintained in the normal incubator.…”
Section: Methodsmentioning
confidence: 99%